2021
DOI: 10.1590/1983-21252021v34n406rc
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity and Ethanol Release to Assess Red Rice Seed Vigor1

Abstract: To evaluate seed vigor, electrical conductivity and ethanol tests are fast and efficient methodologies. They have the potential to be used in several species, such as red rice. However, there are no protocols or information about their efficiency. Thus, the objective was to evaluate the efficiency, and define parameters of execution for electrical conductivity and ethanol tests, to evaluate the vigor of red rice seeds. The study was conducted using four lots of ‘BRS 901’ red rice, which was subjected to a germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…When evaluating electrical conductivity, we observed that the quantity of leachates increased progressively in the direction of the more degraded lots. Inversely proportional to the damage to cellular membranes (Barbosa et al, 2021). The electrical conductivity increase indicates that there was a gradual reduction in seed vigor, this being observed at the level of membrane systems.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…When evaluating electrical conductivity, we observed that the quantity of leachates increased progressively in the direction of the more degraded lots. Inversely proportional to the damage to cellular membranes (Barbosa et al, 2021). The electrical conductivity increase indicates that there was a gradual reduction in seed vigor, this being observed at the level of membrane systems.…”
Section: Resultsmentioning
confidence: 97%
“…The first in the sequence of events during seed deterioration is degradation of the mitochondrial membrane. Therefore, the ideal vigor test should be able to identify reduced seed vigor in the first stages, detecting subtle changes between lots (Barbosa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical conductivity was measured using an electrical conductivity bridge with a cell constant of 1.0. Seed leachate obtained from 50 pre-washed seeds soaked in 50 ml of deionized water for 16 h at room temperature was used for the measurement 18 . Stored rice seed samples were drawn monthly up to twelve months of storage for processing and residue analysis, as outlined in sections “ Processing of rice grains ” and “ Residue analysis ”, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is important to detect the vigor of rice seeds. However, the traditional germination experiment to detect seed vigor is time-consuming and laborious, and other detection methods, such as staining ( Carvalho et al., 2017 ) and electronic conductivity test ( Barbosa et al., 2021 ), will more or less damage and damage seeds, rely on chemical reagents, complex operation, affect seed reuse, at the same time, these detection methods are inefficient, unable to detect rice seed vigor efficiently and non-destructively.…”
Section: Introductionmentioning
confidence: 99%